DESAIN DAN UJI COBA MEDIA PEMBELAJARAN BERBASIS WEBSITE PADA MATERI ASAM BASA - ANAS ILHAM; Zona Octarya (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2018)
ABSTRACTThis research was instigated by the questionnaire result that 51% students of State Senior High School 8 supposed that the Chemistry subject was difficult, and the lack of using educational website.  This research aimed at (1) producing chemistry instructional media website based, (2) knowing validity and practicality level of chemistry instructional media website based on Acid Base Lesson at State Senior High School 8.It was a Research and Development (R&D).  The steps of this research were using Borg & Gall model that was limited to the fifth step—revising the test result.  The mean score of media validation by the material and media experts was 89.58% and it was stated very valid.  In practicality test score done by 5 Chemistry subject teachers, the result was 86.66% showing that chemistry instructional media website based was very practical to be used in facilitating teaching and learning process atState Senior High School 8.  In the test result of 35 students for knowing student response to chemistry instructional media website based, the result was 76.59% showing that the media was on good and proper category to be used. Keywords: Instructional Media, Website, Acid Base, Borg and Gall